View of the Exposition from San Francisco
Description attached: "Magic City Afloat in Bay" That is the appearance here of the 1939 California World's Fairsite as the photographer pictures Treasure Island from San Francisco's Embarcadero. The Sea wall around the Exposition site, however, is 14 feet in height. Across the bay are the hills of Berkeley, and close scrutiny reveal the Campanile and football stadium on the University of California campus. (at right). The 400-foot Tower of the Sun dominates Treasure Island, overlooking the great walls of the exhibit palaces which make of the Exposition a walled city.